Cryptocurrencies and Their Impact on Traditional Monetary Systems: An Exploratory Study - Muslim, Muslim (Advances in Economics & Financial Studies, 2024)
Purpose: This study aims to explore the profound impact of cryptocurrencies on traditional monetary systems, mainly focusing on how they challenge the effectiveness of central banks' monetary policies and contribute to economic instability, especially in emerging markets. Research Design and Methodology: The study employs a qualitative, exploratory research design, drawing on a comprehensive review of existing literature and empirical evidence from emerging markets. The research examines the interactions between cryptocurrencies and traditional financial systems, emphasizing the implications for monetary policy, financial stability, and economic inequality. Findings and Discussion: The findings reveal that the rise of cryptocurrencies significantly diminishes the effectiveness of traditional monetary tools, such as interest rate adjustments and money supply control. This impact is particularly pronounced in emerging markets, where financial infrastructures are less resilient. The study also highlights the risks associated with cryptocurrency volatility, which can exacerbate systemic financial risks and contribute to greater economic inequality. Moreover, the study underscores the urgent need for central banks to innovate, possibly through the development of Central Bank Digital Currencies (CBDCs), to maintain economic stability. Implications: The study suggests that central banks and regulators must adapt to the growing influence of cryptocurrencies by developing new strategies and regulatory frameworks. This adaptation is not just important, but necessary to maintaining financial stability, managing economic inequality, and ensuring the continued relevance of traditional financial institutions in a rapidly evolving digital landscape.